Business advice strategies of immigrant entrepreneurs in Sweden. Issue 1 (5th January 2015) - Yazdanfar, Darush; Abbasian, Saeid; Brouder, Patrick
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine whether there are any significant differences between native Swedish and immigrant entrepreneurs in business advice sought at start-up. Design/methodology/approach – The study, based on a unique and large database consisting of 304 immigrant and 2, 512 native-owned firms, applies several univariate and multivariate statistical methods including ANOVA and regression analysis. Findings – According to the results there are certain similarities and differences between Swedish native- and immigrant-owned firms concerning the type of external business advice they seek. The results suggest there are significant differences between native and immigrant-owned firms for four of 20 types of advice received. Native-owned firms, on average, tend to seek more advice on accounting and on the choice of business form as well as the help of a knowledgeable person. On the other hand, immigrants seek, on average, more advice on export questions than their native counterparts. Research limitations/implications – This research contributes to policy-making by helping authorities gain a better understanding of the impact of immigrant background on business network decisions at the nascent stage of development. Immigrant access to good advice in the nascent stage should increase new firm survival. This study does not, however, measure performance. As this research is based on aggregate level secondary data, more specific analysis has been impossible. This is an important limitation of this paper. In addition, immigrants are not homogenous groups and they differ in age, education, work experiences, etc. The results should therefore be interpreted carefully. Originality/value – This paper is one of the first and few empirical studies investigating the issue of immigrant business advice strategies in the Swedish context. The study provides a detailed overview of how ethnicity influences entrepreneurs' use of external business advice in the firm formation stage for micro and small firms.